Uncovering media agenda a structural topic model of the issue prevalence in Philippine broadsheets. - Pineda, John Pauline M. (Quezon City University of the Philippines, 2019)
Abstract (The agenda-setting framework formulated by Mccombs and Shaw (1972) describes the ability of media organizations to significantly influence the importance placed on the different issues reported in the news. These issues in the agenda which are covered more frequently and prominently by the media are perceived by the public as more important thus effectively shaping their awareness, concern and opinion on such topics. This paper aims to discover the underlying media agenda contained in the Philippine broadsheets. The structural topic model was applied on the unstructured textual contents to determine which important issues were predominantly covered by these individual newspaper, estimate the prevalence for each issue, and identify the factors which influenced such prevalence. The media agenda uncovered by the structural topic model was revealed to have been mainly driven by impactful, relevant and consistent issues generally reflecting social reality, as well as popular, prominent and substantial topics with high news value. The thirty most important topics covered by the Philippine broadsheets and their respective estimated issue prevalence included media contents on the Marawi Siege (5.73%), Duterte Administration, (5.71%), fight against corruption (5.36%), fake news and social media perils (4.85%), West Philippine Sea Dispute (4.77%), embracing nationhood (4.29%), transportation and tourism troubles (4.08%), EJK investigations (4.00%), push for constitutional reforms (3.89%), ASEAN relations (3.72%), Philippine Drug War (3.70%), public health and social services (3.60%), Sereno ouster (3.60%), sensational youth crimes (3.51%), trump and kim (3.40%), peace talks (3.28%), Philippine Economy (2.97%), natural calamities (2.90%), Ombudsman investigations (2.86%), Government Scandals (2.77%), TRAIN and the rising prices (2.64%), foreign affairs (2.63%), triumphs and trials (2.56%), De Lima and Drugs (2.55%), Marco's Burial (2.21%), election and electioneering (1.84%), plight of OFWs (1.83%), food security (1.77%), Duterte's Viral Remarks (1.56%) and dengvaxia controversy (1.40%). Correlation between the issues was observed. Furthermore, each topic was also shown to have been significantly influenced by the various combined effects of the media content source, category, sentiment, length and time period factors, including their interactions.
Thesis ( MS) --University of the Philippines